The causes of sustained load cracking in aluminum 6351-T6 gas cylinders - Cassandre Roos; Jonathan D. Stolk; Wynona Brinkmann; Katelyn Vo; William Skelly (Materials & Design)
Gas cylinders made of the Al-Mg-Si alloy (AA6351) have shown susceptibility to sustained load cracking (SLC) in the neck and shoulder region, which has led to catastrophic, and even fatal, failures. This case study applied computed tomography scanning, optical microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray fluorescence to characterize a large crack in a working gas cylinder and examine the causes of SLC. Results suggest that manufacturing the cylinder by hot forming and subsequent heat treatment causes significant grain growth in the neck region, introduces numerous sub-critical cracks at radial folds on the inside curvature of the neck, and yields high residual stresses in the cylinder cross section. The small cracks at radial folds serve as initiation sites for larger cracks that propagate along grain boundaries and may ultimately cause catastrophic failure of the pressurized cylinder. This study examined several factors that may promote crack propagation, including heavy metal embrittlement, grain size, and residual stress as a result of age hardening. The effectiveness and potential improvement of current regulations and safety testing procedures are also discussed.